Error Analysis of Islamic Primary School (MTs) Students in Resolving Questions on the Materials of Cartesian Coordinate With Malay Culture Nuance in Riau - Bahrin, Bahrin; Maimunah, Maimunah; Roza, Yenita (Universitas Tanjungpura, 2021)
Students experience problems while working in Math, with full of difficulties. They made mistakes in the process of solving questions. The error process that occurred in students leads to the low achievement of the learning outcomes. This research aimed to investigate the mistakes made by MTs students in working on the questions of the Cartesian coordinate integrated with Malay cultural nuances in Riau Province. The study was conducted at MTs in the odd semester of the 2019/2020 academic year. A descriptive approach was used as a research method with a purposive sampling technique. This technique used a test and interview to collect research data. The results of the study described that the errors faced by MTS NurulBilad students included: (1) 55% of misconceptions because students did not understand the concept in the material of Cartesian coordinate (2) procedural errors that 76% of students did not match the stages or steps in the process of drawing on the Cartesian coordinate. Based on the findings, it was hoped that the teacher emphasized more understanding about the concept of Cartesian coordinate.